If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3x + 15 = 0 Reorder the terms: 15 + 3x + 2y = 0 Solving 15 + 3x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + 3x + -15 + 2y = 0 + -15 Reorder the terms: 15 + -15 + 3x + 2y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 3x + 2y = 0 + -15 3x + 2y = 0 + -15 Combine like terms: 0 + -15 = -15 3x + 2y = -15 Add '-2y' to each side of the equation. 3x + 2y + -2y = -15 + -2y Combine like terms: 2y + -2y = 0 3x + 0 = -15 + -2y 3x = -15 + -2y Divide each side by '3'. x = -5 + -0.6666666667y Simplifying x = -5 + -0.6666666667y
| 6(2m+3)-4=2(5m+4)+m | | 3x^2-3x-2=18 | | 15=x/-2 | | 9x-7=6x-13 | | 4[log(x)+8]=11 | | 7h/12-4h/12 | | 3x=29-4y | | -72+6x+x^2=0 | | 4.5(5)=5x | | x-24/x | | (5x+1)(2x-3)=4x(x-5) | | 2x=-4+2y | | 6ln(2x+4)=22 | | 15y-3x=-9 | | 3y-15x=-9 | | U=2(7n+30)+9(n+1) | | -7u+4(u-5)=-11 | | 7m+12=6-m | | 7m+12=6m | | a^5-3a^2/3a^2 | | 6ln(4x+4)=28 | | 64x^6-24x^4+18x^2-27=0 | | -2+j=-11 | | 3x-32=7-x+28 | | 7-7/2x=-5 | | -34+-4d=10 | | 483+60x=843 | | 3x+38=360 | | -1=v+6-2 | | 3x+38=180 | | 7(1-4r)=-133 | | 6log(4x+4)=28 |